Deeds and Words: Farmers' Attitude-Paradox in Collective Action for Small-Scale Irrigation - Miao, Shanshan; Zhu, Xueqin; Heijman, Wim; Xu, Zengwei; Lu, Qian (International journal of environmental research and public health, 2022)
We explore the mechanisms of the attitude-behavior paradox and how multiple stakeholders strategize to compromise their attitudes and behaviors. Through an instrumental variable probit model, we examine the effect of income heterogeneity and social ties on the farmers' attitude-behavior paradox for collective action. The empirical results demonstrate that weak and strong ties, income heterogeneity, interaction terms, education, community environment, and community rules negatively affect the paradox, whereas water stealing and water use conflicts positively affect it. After dividing the paradox into two forms, we find that weak ties, the interaction terms thereof, negatively affect the paradox for "having negative attitude but do have behavior", while income heterogeneity negatively affects the paradox for "having positive attitude but no behavior". We contribute to the understanding of mechanisms whereby economic incentives and social structures interplay in addressing the above paradox. We conclude by discussing the implications for policies to overcome this social dilemma.
Keywords: Farmers; Attitude; Environment; životní prostředí; voda; Agriculture; lidé; Water; postoj; zemědělství; zemědělci; Humans